Novel Therapeutic Strategies in the Management of Non-Variceal Upper Gastrointestinal Bleeding - Ari Garber (Clinical Endoscopy, 2016)
Non-variceal upper gastrointestinal bleeding, the most common etiology of which is peptic ulcer disease, remains a persistent challenge despite a reduction in both its incidence and mortality. Both pharmacologic and endoscopic techniques have been developed to achieve hemostasis, with varying degrees of success. Among the pharmacologic therapies, proton pump inhibitors remain the mainstay of treatment, as they reduce the risk of rebleeding and requirement for recurrent endoscopic evaluation. Tranexamic acid, a derivative of the amino acid lysine, is an antifibrinolytic agent whose role requires further investigation before application. Endoscopically delivered pharmacotherapy, including Hemospray (Cook Medical), EndoClot (EndoClot Plus Inc.), and Ankaferd Blood Stopper (Ankaferd Health Products), in addition to standard epinephrine, show promise in this regard, although their mechanisms of action require further investigation. Non-pharmacologic endoscopic techniques use one of the following two methods to achieve hemostasis: ablation or mechanical tamponade, which may involve using endoscopic clips, cautery, argon plasma coagulation, over-the-scope clipping devices, radiofrequency ablation, and cryotherapy. This review aimed to highlight these novel and fundamental hemostatic strategies and the research supporting their efficacy.